CRITICAL ISSUE TAX PLANNING: AGRESIVITAS DAN PENGHINDARAN PAJAK PELAKU USAHA KECIL DAN MENENGAH - Sri Anugrah Natalina; Sayekti Indah Kusumawardhany2 (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Purpose: Tax avoidance and tax aggressiveness are widely interpreted as actions of taxpayers who do not violate tax rules, as evidenced by taxpayers still reporting and paying taxes, but the amount paid is less than the actual value. Findings: This legal act is because the tax calculation report and the value paid are the same, it becomes illegal because the value reported for tax has been made less than the actual value, or minimizes profits. Results:  MSME actors in Kediri City show that socialization and knowledge have a positive and significant influence on the awareness of MSME actors in carrying out tax payments. This can be used as a measure that tax planning practices for MSME actors with the aim of aggressiveness and tax avoidance do not occur, but to generate tax savings.  Implication: With the improvement of forms of socialization and increased knowledge, taxpayer awareness of MSME actors is created, it is hoped that MSME actors can actively contribute to tax payments.